Hypertension among non-insulin-dependent diabetes mellitus (NIDDM) patients at OPD Diabetic Clinics in Srinagarind and Khon Kaen Hospitals, Khon Kaen, Thailand - Suwandee, Ratchanee
This cross-sectional study estimated the prevalence of hypertension among non-insulin-dependent diabetes mellitus (NIDDM) patients, compared the prevalence of hypertension among categories of selected socio-demographic, behavioral and medical factors; and determined the association between hypertension and selected behavioral factors, namely, alcohol consumption, cigarette smoking and salt intake. The study was conducted among 639 NIDDM patients aged 30 years old and over who consulted at the Out Patient Diabetic Clinics and Srinagarind and Khon Kaen Hospitals in Khon Kaen, Thailand from February to June 1999.The prevalence of hypertension among the study population was 31.4(95CI 34-48). The prevalence of hypertension wsa highest among the = 65 year-old respondents (38.4, 95CI 29-48). It was higher among females (36.1, 95CI 32-41) than in males (28.7, 95CI 22-36), among those with low education (35.2, 95CI 31.39) compared with high education (17.5, 95CI 8-33), among overweights (i.e., with BMI23 kg/m?) than the non-overweights (40, 95CI 35-45versus 20.9, 95CI 16-27), and among those who were undergoing diabetic treatment without insulin (35.0, 95CI 31-39) compared with those given insulin (29.9, 95CI 21-40).The results of logistic regression analysis showed that age, duration of diabetes and BMI status modified the effect of alcohol consumption on hypertension. The OR for hypertension among alcohol drinkers relative to non-drinkers was highest among the 55-64-year-old subjects while the ORs were almost the same between the 30-54 and = 65 years old. The absence of a monotonic relationship between age and hypertension prevalence could be due to chance, survivor or misclassification biases.The magnitude of ORs increased with increasing diabetes chronicity. The data further suggested that increased body weight further increased the risk of hypertension especially among the 55-64-year-old chronically diabetic (i.e., diabetes duration of 5 years or longer) patients. The results clearly suggested the importance of controlling body weight among relatively older, alcohol-drinking NIDDM patients who have been diabetics for longer than four years. The odds of hypertension among this already high-risk drinkers was between 8-10 times that of the odds among non-alcohol drinkers. Although this study did not purposely investigate (as an exposure variable of interest) the role of body mass index on hypertension, these results revealed that excess weight considerably increased the odds of hypertension among this particular group of subjects.The ORs among non-overweights were in general lower than the ORs among overweight subjects. In a few instances, alcohol even appeared to offer some protection against hypertension among non-overweight NIDDM patients. Since obesity and excessive alcohol consumption are also known to be associated with diseases other than hypertension among NIDDM patients, it is quite prudent to emphasize to NIDDM patients the importance of modifying these two high-risk behaviors.